[Measurement-Based Procurement Approach for Biosimilars in Italy: A Position Paper] - Cavaliere, Arturo; Mennini, Francesco Saverio; Pani, Marcello; Torrico, Paolo Gennaro; Torrisi, Salvatore (Farmeconomia. Health Economics and Therapeutic Pathways, 2023)
The full potential of biosimilars has not been achieved yet, and this document has been written with the aim of methodizing an effective and measurable procurement system that ensures wider, simplified, and economically sustainable access of biosimilars to patients. The economic and financial sustainability generated by the increased use of biosimilars for the benefit of patients and society has been estimated and confirmed in several observational studies and probabilistic projections conducted in Europe. Despite differences in procurement policies, significant reductions in spending for some biosimilars have been recorded in several European countries between 2015 and 2018 compared with the period preceding the patent’s expiry. An accurate evaluation of the economic outcomes resulting from an extended use of biosimilars has also been conducted in Italy, with the settled purpose of calculating the combined effects that various biosimilars with patent expired have generated and will generate in terms of overall spending reduction. Even with the limitations typically associated with probabilistic models, it is also evident that an expanded use of biosimilars is an effective tool to govern the expenditure and channel resources to support the intrinsic balance of the health system (i.e., sustainability) or to ensure the introduction of innovative drugs or diagnostic procedures (i.e., accessibility). The economic sustainability of the health system must also be achieved through the maintenance of a competitive procurement system. This requires a serious reconsideration of the purchasing criteria. The principle of competitiveness can contribute to the governance, containment, reduction or streamlining of public expenditure on biosimilars, but it is appropriate to establish which factors can feed and support a lawful competition, actually. Competition merely based on price reduction between biosimilar and biosimilar, excluding, undervaluing, or taking for granted that between originator and biosimilar, leads to a price erosion and this condition could have unpredictable and undesirable consequences. The market must have its own balance to be of interest to manufacturing companies and ensure the competitiveness. In the field of biosimilars, as in other areas, the need to move from purchasing criteria based on cost exclusively to those based on overall economic benefit by combining price with quality is generally shared. This approach allows for a balanced competition on multiple parameters and above all enables the best service to be provided to patients and the National Health Service. Hence, what are the quality criteria to be considered in relation to price? The areas relevant to the procurement code regulations, the determination of needs, the technical-market knowledge, the encoding of quality criteria, and their specific parameterization to the contingent dynamics of the market must certainly be identified and examined: this is what the present document aims to do. The intention is to provide a guide that can facilitate the implementation of tenders awardable by evaluating the economically most advantageous offer and that will enable us to measure the effect of a “new” procurement system, comparing the differences between what is recorded now and what is detected in the phase following the introduction of quality-price ratio-based tenders for biosimilars in Italy. In conclusion, through the joint work of specialists and experts in the sector, this Position Paper identifies the quality criteria for evaluating biosimilars and proposes a technical specification based on identified criteria, so as to provide central purchasing bodies and institutional payers with a strategy for the actual implementation both at regional and national level of a procurement method focusing on the quality-price ratio.The full potential of biosimilars has not been achieved yet, and this document has been written with the aim of methodizing an effective and measurable procurement system that ensures wider, simplified, and economically sustainable access of biosimilars to patients. The economic and financial sustainability generated by the increased use of biosimilars for the benefit of patients and society has been estimated and confirmed in several observational studies and probabilistic projections conducted in Europe. Despite differences in procurement policies, significant reductions in spending for some biosimilars have been recorded in several European countries between 2015 and 2018 compared with the period preceding the patent’s expiry. An accurate evaluation of the economic outcomes resulting from an extended use of biosimilars has also been conducted in Italy, with the settled purpose of calculating the combined effects that various biosimilars with patent expired have generated and will generate in terms of overall spending reduction. Even with the limitations typically associated with probabilistic models, it is also evident that an expanded use of biosimilars is an effective tool to govern the expenditure and channel resources to support the intrinsic balance of the health system (i.e., sustainability) or to ensure the introduction of innovative drugs or diagnostic procedures (i.e., accessibility). The economic sustainability of the health system must also be achieved through the maintenance of a competitive procurement system. This requires a serious reconsideration of the purchasing criteria. The principle of competitiveness can contribute to the governance, containment, reduction or streamlining of public expenditure on biosimilars, but it is appropriate to establish which factors can feed and support a lawful competition, actually. Competition merely based on price reduction between biosimilar and biosimilar, excluding, undervaluing, or taking for granted that between originator and biosimilar, leads to a price erosion and this condition could have unpredictable and undesirable consequences. The market must have its own balance to be of interest to manufacturing companies and ensure the competitiveness. In the field of biosimilars, as in other areas, the need to move from purchasing criteria based on cost exclusively to those based on overall economic benefit by combining price with quality is generally shared. This approach allows for a balanced competition on multiple parameters and above all enables the best service to be provided to patients and the National Health Service. Hence, what are the quality criteria to be considered in relation to price? The areas relevant to the procurement code regulations, the determination of needs, the technical-market knowledge, the encoding of quality criteria, and their specific parameterization to the contingent dynamics of the market must certainly be identified and examined: this is what the present document aims to do. The intention is to provide a guide that can facilitate the implementation of tenders awardable by evaluating the economically most advantageous offer and that will enable us to measure the effect of a “new” procurement system, comparing the differences between what is recorded now and what is detected in the phase following the introduction of quality-price ratio-based tenders for biosimilars in Italy. In conclusion, through the joint work of specialists and experts in the sector, this Position Paper identifies the quality criteria for evaluating biosimilars and proposes a technical specification based on identified criteria, so as to provide central purchasing bodies and institutional payers with a strategy for the actual implementation both at regional and national level of a procurement method focusing on the quality-price ratio.